Graphite negative electrode material and preparation method thereof, electrode sheet and electrochemical device
By performing the method of adding asphalt twice and heat treatment to the raw material coke twice, the graphite negative electrode material obtained solves the problem that existing materials cannot take into account high energy density and long cycle performance, and achieves both high energy density and long cycle performance.
Patent Information
- Application Number
- CN202411976447.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
Existing graphite negative electrode materials cannot take into account high energy density and long cycle performance, resulting in a low capacity retention rate.
By performing the first heat treatment of the mixture A (raw material coke and first bitumen) to obtain a first carbon material, and then performing a second heat treatment and graphitization of the first carbon material and the second bitumen to obtain a graphite negative electrode material. This method improves the isotropy and surface characteristics of the material by adding asphalt twice and heat treatment twice.
The resulting graphite negative electrode material has good isotropy and high compaction density, which can take into account high energy density and long cycle performance, improving the overall performance of the battery.
Smart Images

Figure CN119786568A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a graphite negative electrode material and a preparation method thereof, a pole piece and an electrochemical device. Background Art
[0002] The limited supply of fossil fuels and global warming are promoting the development of electric vehicles (EVs), and lithium-ion batteries are widely used in many fields such as portable devices and electric vehicles. Among them, consumer electronic products have increasingly higher requirements for the energy density and cycle performance of graphite negative electrodes.
[0003] In order to obtain long-cycle, high-energy-density graphite negative electrode materials, raw materials such as needle coke are usually used to manufacture secondary particle artificial graphitized materials to meet both energy density and cycle performance requirements.
[0004] Chinese patent application CN115893401A uses negative electrode raw materials and water-soluble binders to mix evenly, then add water and stir to obtain wet materials, pelletize the wet materials to obtain a spherical mixture, and then dry the pellets. The dried pellets are subjected to high-temperature graphitization, and then crushed and screened to obtain secondary particle artificial graphite negative electrode materials. This method improves the cycle performance of artificial graphitized negative electrode materials and improves the safety of the processing process by graphitizing after pelletization, but the re-crushing process of the pellets after graphitization increases the surface defects of the negative electrode material, and the specific surface area is large, resulting in a low capacity retention rate.
[0005] Chinese patent application CN115784221A uses a precursor and a binder to mix at room temperature, then granulate at high temperature under inert gas protection conditions, and then cool to obtain a secondary granular material. The cooled secondary granular material is spilt and depolymerized, and then graphitized to obtain a long-cycle secondary granular artificial graphite negative electrode material. The secondary granular artificial graphitized negative electrode material obtained by granulation has better improved cycle performance, but the capacity is low, and it is difficult to simultaneously take into account the high energy density requirements.
[0006] Therefore, it is urgent to develop a graphite negative electrode material that can achieve both high energy density and long cycle performance. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the defect that the graphite negative electrode material in the prior art cannot have both high energy density and long cycle performance, and provide a graphite negative electrode material and its preparation method, a pole piece and an electrochemical device. The battery assembled with the graphite negative electrode material prepared by the present invention can have both high energy density and long cycle performance.
[0008] The present invention solves the above technical problems through the following technical solutions.
[0009] The present invention provides a method for preparing a graphite negative electrode material, which comprises the following steps:
[0010] S1. Performing a first heat treatment on a mixture A to obtain a first carbon material; the mixture A comprises raw coke and a first pitch, the mass ratio of the raw coke to the first pitch is 1:(1-5); the D50 of the raw coke is 7-9 μm;
[0011] S2. subjecting B to a second heat treatment and a graphitization treatment in sequence to obtain the graphite negative electrode material; the mixture B comprises the first carbon material and the second asphalt.
[0012] In S1 of the present invention, the type of the raw coke can be conventional in the art, preferably including one or more of petroleum coke, pitch coke, needle coke and calcined coke, such as petroleum coke and / or calcined coke. The calcined coke refers to the product of petroleum coke calcined at a high temperature of 1300 degrees without contact with oxygen.
[0013] In S1 of the present invention, the residual carbon content of the raw coke may be >90%, preferably greater than 92%, for example ≥99%. The residual carbon content is calculated by the mass change of the raw coke before and after calcination at 1000±100°C in a nitrogen atmosphere.
[0014] In S1 of the present invention, D50 of the raw coke is preferably 8-9 μm, for example 8.5 μm.
[0015] In the present invention, the first asphalt and the second asphalt are each independently graphitizable asphalt. The graphitizable asphalt means that the asphalt is carbonized at 1000°C for 3 hours, crushed to a D50 of 10-15 μm, and then graphitized at 3000°C for 2 hours to obtain a negative electrode material, and the negative electrode material is mixed with a conductive agent, sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 95.5:1.5:1.5:1.5, and applied on a copper foil, with a compaction density of 1.7 g / cm 3 , vacuum dried as the negative electrode, lithium metal as the counter electrode, the electrolyte uses a mixture of 1M LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) in a mass ratio of 1:1, and the separator is a PE / PP / PE composite film, assembled into a button cell; the button cell is charged and discharged on a blue battery tester at a rate of 0.1C, and the first discharge specific capacity is greater than or equal to 340mAh / g of asphalt. The conductive agent is preferably KS-6.
[0016] In the present invention, preferably, the softening point of the second asphalt is greater than the softening point of the first asphalt. More preferably, the softening point of the second asphalt is 30-50°C greater than the softening point of the first asphalt.
[0017] In S1 of the present invention, the type of the first asphalt may be conventional in the art, and preferably includes one or more of petroleum asphalt, coal asphalt, modified asphalt and synthetic asphalt, such as petroleum asphalt.
[0018] In S1 of the present invention, the softening point of the first asphalt is preferably 120-150°C, such as 130 or 140°C.
[0019] In S1 of the present invention, the mass ratio of the raw coke to the first asphalt is preferably 1:(2-4), such as 1:3 or 1:3.5.
[0020] In S1 of the present invention, the mixture A is preferably obtained by mixing the raw coke and the first asphalt. The mixing time is preferably 30-90 minutes, such as 60 minutes.
[0021] In S1 of the present invention, the first heat treatment is preferably performed under an inert atmosphere, and the inert atmosphere is preferably nitrogen.
[0022] In S1 of the present invention, the temperature of the first heat treatment may be 200-650°C, preferably 200-400°C, such as 300 or 350°C.
[0023] In S1 of the present invention, the time of the first heat treatment may be 1-10 hours, for example 3 hours.
[0024] In S1 of the present invention, the first heat treatment preferably includes a first heat treatment and a second heat treatment performed sequentially, and the temperature of the second heat treatment is higher than the temperature of the first heat treatment.
[0025] The temperature of the first heat treatment is preferably 200-300° C., such as 250° C. The time of the first heat treatment is preferably 1-5 h, such as 2 h.
[0026] The temperature of the second stage heat treatment is preferably 300-400° C., such as 350° C. The time of the second stage heat treatment is preferably 1-5 h, such as 2 h.
[0027] In S2 of the present invention, the type of the second asphalt can be conventional in the art, preferably including one or more of petroleum asphalt, coal asphalt, modified asphalt and synthetic asphalt, such as petroleum asphalt.
[0028] In S2 of the present invention, the softening point of the second asphalt is preferably 120-200°C, such as 150 or 180°C.
[0029] In S2 of the present invention, the mixture of the first carbon material and the second pitch is preferably obtained by mixing the first carbon material and the second pitch. The mixing time is preferably 30-90 minutes, for example 60 minutes.
[0030] In S2 of the present invention, the mass ratio of the first carbon material to the second asphalt may be 100:(5-20), preferably 100:(7-15), for example 100:10 or 100:12.
[0031] In S2 of the present invention, the second heat treatment is preferably performed under an inert atmosphere, and the inert atmosphere is preferably nitrogen.
[0032] In S2 of the present invention, the temperature of the second heat treatment may be 250-650°C, preferably 250-600°C, such as 300 or 550°C.
[0033] In S2 of the present invention, the time of the second heat treatment may be 1-10 h, for example, 2, 3, 3.5, 5, 6 or 6.5 h.
[0034] In S2 of the present invention, the second heat treatment preferably includes a three-stage heat treatment and a four-stage heat treatment performed sequentially, and the temperature of the four-stage heat treatment is higher than the temperature of the three-stage heat treatment.
[0035] The temperature of the three-stage heat treatment is preferably 250-350° C., such as 300° C. The time of the three-stage heat treatment is preferably 1-5 hours, such as 3 hours.
[0036] The temperature of the four-stage heat treatment is preferably 400-600° C., such as 550° C. The time of the four-stage heat treatment is preferably 1-5 h, such as 2, 3 or 3.5 h.
[0037] In S2 of the present invention, the temperature of the graphitization treatment may be 2500-3000°C, for example 2800°C.
[0038] In S2 of the present invention, the graphitization treatment time may be 2-4 hours, for example 3 hours.
[0039] The present invention also provides a graphite negative electrode material, which is prepared by the method for preparing the graphite negative electrode material as described above.
[0040] The present invention also provides a graphite negative electrode material, wherein the graphite negative electrode material is a secondary particle, the pole piece OI value of the graphite negative electrode material is 7-9.2; the D50 of the graphite negative electrode material is 15-19 μm; the compaction density of the graphite negative electrode material is 1.9-2.1 g / cm 3 .
[0041] In the present invention, the D50 of the graphite negative electrode material is preferably 15.21-18.79 μm, such as 18.02 or 16.89 μm.
[0042] In the present invention, the compaction density of the graphite negative electrode material is, for example, 2.011, 1.995, 1.933 or 1.926 g / cm 3 .
[0043] In the present invention, the pole piece OI value of the graphite negative electrode material is preferably 7.5-9.1, such as 8.6, 7.8 or 8.8. The pole piece OI value of the graphite negative electrode material can be obtained by testing the following method: the graphite negative electrode material is mixed evenly with a conductive agent, sodium carboxymethyl cellulose (CMC), and styrene butadiene rubber (SBR) in a mass ratio of 95.5:1.5:1.5:1.5, and applied on a copper foil with a compaction density of 1.7 g / cm 3 , vacuum dried and used as negative electrode; the negative electrode was sliced and the graphite 004 and 110 peak areas were tested on an X-ray diffractometer, and the 004 peak area / 110 peak area was the pole piece OI value of the graphite negative electrode material. The conductive agent is preferably KS-6.
[0044] The present invention also provides a pole piece, which comprises the graphite negative electrode material as described above.
[0045] The present invention also provides an electrochemical device, which comprises the pole piece as described above.
[0046] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0047] The reagents and raw materials used in the present invention are commercially available.
[0048] The positive and progressive effects of the present invention are:
[0049] (1) The present invention can obtain a graphite negative electrode material by adding asphalt twice and performing heat treatment twice on raw coke; the addition of the first asphalt can modify the surface defects of the raw coke, and the addition of the second asphalt can improve the isotropy of the raw coke. The raw coke is finally processed to become raw coke graphite, and the asphalt is finally processed to become asphalt graphite. The graphite negative electrode material finally obtained is secondary particles, and the asphalt graphite is distributed in the particle gaps of the raw coke graphite and coated on the surface of the raw coke graphite.
[0050] (2) The graphite negative electrode material prepared by the present invention has good isotropy, which is manifested as a small pole piece OI value. Furthermore, the graphite negative electrode material also has a high compaction density (for example, a compaction density of 1.9-2.1 g / cm 3 ).
[0051] (3) The battery made from this graphite negative electrode material can have both high energy density and long cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1The figure is a flow chart for preparing the graphite negative electrode material according to an embodiment of the present invention.
[0053] Figure 2 Schematic diagram of the structure of the graphite negative electrode material prepared in an embodiment of the present invention.
[0054] Description of reference numerals:
[0055] Raw materials: coke graphite-1; asphalt graphite-2. DETAILED DESCRIPTION
[0056] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0057] Figure 1 The figure is a flow chart for preparing the graphite negative electrode material of the following embodiment.
[0058] Figure 2 Schematic diagram of the structure of the graphite negative electrode material prepared in the following embodiment.
[0059] In the following examples or comparative examples, the calcined coke used refers to the product obtained by calcining petroleum coke at a high temperature of 1300 degrees without contact with oxygen.
[0060] Example 1
[0061] S1. (1) Calcined coke with a D50 of 9 μm (residual carbon content ≥ 99%, purchased from Jinzhou Petrochemical) and first asphalt (petroleum asphalt with a softening point of 120° C.) were mixed at a mass ratio of 100:5 for 60 minutes to obtain a mixture A.
[0062] (2) The mixture A obtained in step (1) of S1 is subjected to a first heat treatment under nitrogen protection, with a first heat treatment at 200° C. for 1 hour and a second heat treatment at 350° C. for 2 hours to obtain a first carbon material.
[0063] S2. (1) Mix the first carbon material obtained in step (2) of S1 with a second asphalt (petroleum asphalt with a softening point of 150° C.) at a mass ratio of 100:12 for 60 minutes to obtain a mixture of the first carbon material and the second asphalt.
[0064] (2) The mixture of the first carbon material and the second asphalt obtained in step S2 (1) is subjected to a second heat treatment under nitrogen protection, with three stages of heat treatment at 250° C. for 3 hours and four stages of heat treatment at 550° C. for 3 hours.
[0065] (3) The material obtained in step (2) of S2 is graphitized at 3000° C. for 3 hours, and then sieved to obtain a graphite negative electrode material.
[0066] Example 2
[0067] S1. (1) Calcined coke (residual carbon content ≥ 99%, purchased from Jinzhou Petrochemical) with a D50 of 8.5 μm and a first asphalt (petroleum asphalt with a softening point of 150° C.) were mixed at a mass ratio of 100:3.5 for 60 minutes to obtain a mixture A.
[0068] (2) The mixture A obtained in step (1) of S1 is subjected to a first heat treatment under nitrogen protection, with a first heat treatment at 200° C. for 1 hour and a second heat treatment at 350° C. for 2 hours to obtain a first carbon material.
[0069] S2. (1) Mix the first carbon material obtained in step (2) of S1 with a second asphalt (petroleum asphalt with a softening point of 200° C.) at a mass ratio of 100:10 for 60 minutes to obtain a mixture of the first carbon material and the second asphalt.
[0070] (2) The mixture of the first carbon material and the second asphalt obtained in step S2 (1) is subjected to a second heat treatment under nitrogen protection, with three stages of heat treatment at 300° C. for 3 hours and four stages of heat treatment at 550° C. for 3 hours.
[0071] (3) The material obtained in step (2) of S2 is graphitized at 3000° C. for 3 hours, and then sieved to obtain a graphite negative electrode material.
[0072] Example 3
[0073] S1. (1) Mix needle coke (residual carbon content: 92%) with a D50 of 8.5 μm and a first pitch (petroleum pitch with a softening point of 120° C.) at a mass ratio of 100:4 for 60 minutes to obtain a mixture A.
[0074] (2) The mixture A obtained in step (1) of S1 is subjected to a first heat treatment under nitrogen protection, with a first heat treatment at 200° C. for 1 hour and a second heat treatment at 350° C. for 2 hours to obtain a first carbon material.
[0075] S2. (1) Mix the first carbon material obtained in step (2) of S1 with the second asphalt (petroleum asphalt with a softening point of 200° C.) at a mass ratio of 100:7 for 60 minutes to obtain a mixture of the first carbon material and the second asphalt.
[0076] (2) The mixture of the first carbon material and the second asphalt obtained in step S2 (1) is subjected to a second heat treatment under nitrogen protection, with three stages of heat treatment at 300°C for 3 hours and four stages of heat treatment at 550°C for 3.5 hours.
[0077] (3) The material obtained in step (2) of S2 is graphitized at 3000° C. for 3 hours, and then sieved to obtain a graphite negative electrode material.
[0078] Example 4
[0079] The only difference from Example 3 is that the softening points of the first asphalt in step S1(1) and the second asphalt in step S2(1) are both 120°C.
[0080] Comparative Example 1
[0081] S1. (1) mixing calcined coke (residual carbon content ≥ 99%, purchased from Jinzhou Petrochemical) with a D50 of 9 μm and a first asphalt (petroleum asphalt with a softening point of 150° C.) at a mass ratio of 100:19 for 60 minutes to obtain a mixture A;
[0082] (2) The mixture A obtained in step (1) of S1 is subjected to a first heat treatment under nitrogen protection, a first heat treatment at 300° C. for 3 hours, a second heat treatment at 550° C. for 4.5 hours, and then graphitized at 3000° C. for 3 hours, followed by screening to obtain a graphite negative electrode material.
[0083] Comparative Example 2
[0084] S1. (1) Mix needle coke with a D50 of 8.5 μm (residual carbon content of 92%) with a first asphalt (petroleum asphalt with a softening point of 120°C) and a second asphalt (petroleum asphalt with a softening point of 200°C) in a mass ratio of 100:4:10 for 60 minutes to obtain a mixture A.
[0085] (2) The mixture A obtained in step (1) of S1 is subjected to a first heat treatment under nitrogen protection, a first heat treatment at 200° C. for 3 hours, a second heat treatment at 550° C. for 4.5 hours, and then graphitized at 3000° C. for 3 hours, followed by screening to obtain a graphite negative electrode material.
[0086] Comparative Example 3
[0087] The only difference from Example 3 is that in step S1(1), the mass ratio of needle coke to the first asphalt is 100:12.5.
[0088] Comparative Example 4
[0089] The only difference from Example 3 is that step S1(1) is: needle coke with a D50 of 8.5 μm is mixed with a phenolic resin (purchased from Shandong Shengquan Group, with a number average molecular weight of 1000-2500) and a first asphalt (asphalt with a softening point of 120°C) in a mass ratio of 100:4:4 for 60 minutes to obtain a mixture A.
[0090] Comparative Example 5
[0091] The only difference from Example 3 is that in step S1(1), the D50 of the raw coke is 6 μm.
[0092] Effect Example 1
[0093] The D50 particle size of the graphite negative electrode materials prepared in Examples 1-4 and Comparative Examples 1-5 was tested using a Malvern particle size tester. The compaction density of the graphite negative electrode materials prepared in Examples 1-4 and Comparative Examples 1-5 was tested using a force test universal testing machine. The results are shown in Table 1.
[0094] Table 1
[0095]
[0096]
[0097] The preparation method of the button cell used for testing the electrochemical performance is as follows: the graphite negative electrode materials prepared in Examples 1-4 and Comparative Examples 1-5 are respectively mixed with a conductive agent (KS-6), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a mass ratio of 95.5:1.5:1.5:1.5, and coated on a copper foil with a compaction density of 1.7 g / cm 3 , vacuum dried as the negative electrode, lithium metal as the counter electrode, the electrolyte is a mixture of 1M LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) in a mass ratio of 1:1, and the separator is a PE / PP / PE composite film, assembled into a button battery. The above button battery was tested for various electrical properties on a blue battery tester, and the test conditions were: charge and discharge at a current density of 0.1C, and the charge and discharge voltage was 0.005-2V.
[0098] (1) First discharge specific capacity and first coulombic efficiency
[0099] Charge and discharge were carried out at a rate of 0.1C to test the first discharge specific capacity and the first coulombic efficiency.
[0100] (2) Cycle performance
[0101] The charge and discharge cycle was performed 300 times at a rate of 0.1C, and the 300th discharge specific capacity was recorded as the 300-cycle retention capacity. The 300-cycle retention rate = 300th cycle retention capacity / first discharge specific capacity × 100%.
[0102] (3) Pole piece OI value: The negative electrode prepared above was sliced and the graphite 004 and 110 peak areas were measured on an X-ray diffractometer. The 004 peak area / 110 peak area was the OI value.
[0103] The test results are shown in Table 2.
[0104] Table 2
[0105]
[0106]
[0107] It can be seen from the above table that, compared with comparative examples 1-5, the batteries made of the graphite negative electrode materials of embodiments 1-4 can have both high capacity (up to 353 mAh / g or more) and long cycle performance (up to 97% or more).
Claims
1. A method for preparing a graphite negative electrode material, characterized in that: It includes the following steps: S1. Performing a first heat treatment on a mixture A to obtain a first carbon material; the mixture A comprises raw coke and a first pitch, the mass ratio of the raw coke to the first pitch is 1:(1-5); the D50 of the raw coke is 7-9 μm; S2. Subjecting the mixture B to a second heat treatment and a graphitization treatment in sequence to obtain the graphite negative electrode material; the mixture B includes the first carbon material and the second asphalt.
2. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: The preparation method of the graphite negative electrode material meets one or more of the following conditions: A. The softening point of the second asphalt is greater than the softening point of the first asphalt; preferably, the softening point of the second asphalt is 30-50°C greater than the softening point of the first asphalt; B. In S1, the mass ratio of the raw coke to the first asphalt is 1:(2-4), for example, 1:3 or 1:3.5; In C and S1, the D50 of the raw coke is 8-9 μm, for example 8.5 μm; In D and S2, the mass ratio of the first carbon material to the second asphalt is 100:(5-20), preferably 100:(7-15), for example 100:10 or 100:
12.
3. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: The preparation method of the graphite negative electrode material meets one or more of the following conditions: In A and S1, the type of the raw coke includes one or more of petroleum coke, pitch coke, needle coke and calcined coke, such as petroleum coke and / or calcined coke; In B and S1, the residual carbon content of the raw coke is > 90%, preferably greater than 92%, for example ≥ 99%; C. The first asphalt and the second asphalt are each independently graphitizable asphalt; In D and S1, the type of the first asphalt includes one or more of petroleum asphalt, coal asphalt, modified asphalt and synthetic asphalt, such as petroleum asphalt; In E and S1, the softening point of the first asphalt is 120-150°C, for example, 130 or 140°C; In F and S1, the first heat treatment is performed under an inert atmosphere; the inert atmosphere is preferably nitrogen; In G and S1, the temperature of the first heat treatment is 200-650°C, preferably 200-400°C, for example 300 or 350°C; In H and S1, the time of the first heat treatment is 1-10 hours, for example, 3 hours.
4. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: The preparation method of the graphite negative electrode material meets one or more of the following conditions: In A and S2, the type of the second asphalt includes one or more of petroleum asphalt, coal asphalt, modified asphalt and synthetic asphalt, such as petroleum asphalt; In B and S2, the softening point of the second asphalt is 120-200°C, such as 150 or 180°C; C. In S2, the second heat treatment is performed under an inert atmosphere; the inert atmosphere is preferably nitrogen; In D and S2, the temperature of the second heat treatment is 250-650°C, preferably 250-600°C, such as 300 or 550°C; In E and S2, the second heat treatment time is 1-10 h, for example, 2, 3, 3.5, 5, 6 or 6.5 h; In F and S2, the temperature of the graphitization treatment is 2500-3000° C., for example, 2800° C.; In G and S2, the graphitization treatment time is 2-4 hours, for example, 3 hours.
5. The method for preparing a graphite negative electrode material according to claim 3 or 4, characterized in that: The preparation method of the graphite negative electrode material meets one or more of the following conditions: In A, S1, the first heat treatment includes a first heat treatment and a second heat treatment performed sequentially, and the temperature of the second heat treatment is higher than the temperature of the first heat treatment; The temperature of the heat treatment is preferably 200-300°C, such as 250°C; the time of the heat treatment is preferably 1-5h, such as 2h; The temperature of the second heat treatment is preferably 300-400°C, such as 350°C; the time of the second heat treatment is preferably 1-5h, such as 2h; B. In S2, the second heat treatment includes a three-stage heat treatment and a four-stage heat treatment performed sequentially, and the temperature of the four-stage heat treatment is higher than the temperature of the three-stage heat treatment; The temperature of the three-stage heat treatment is preferably 250-350°C, such as 300°C; the time of the three-stage heat treatment is preferably 1-5h, such as 3h; The temperature of the four-stage heat treatment is preferably 400-600°C, such as 550°C; the time of the four-stage heat treatment is preferably 1-5h, such as 2, 3 or 3.5h.
6. A graphite negative electrode material, characterized in that: The negative electrode material is prepared by the method for preparing the graphite negative electrode material according to any one of claims 1 to 5.
7. A graphite negative electrode material, characterized in that: The graphite negative electrode material is a secondary particle, and the pole piece OI value of the graphite negative electrode material is 7-9.2; the D50 of the graphite negative electrode material is 15-19 μm; the compaction density of the graphite negative electrode material is 1.9-2.1 g / cm 3 .
8. The graphite negative electrode material according to claim 7, characterized in that The graphite negative electrode material meets one or more of the following conditions: A. The D50 of the graphite negative electrode material is 15.21-18.79 μm, for example 18.02 or 16.89 μm; B. The OI value of the pole piece of the graphite negative electrode material is 7.5-9.1, such as 8.6, 7.8 or 8.8; C. The compaction density of the graphite negative electrode material is 2.011, 1.995, 1.933 or 1.926 g / cm 3 .
9. A pole piece, characterized in that: It comprises the graphite negative electrode material as claimed in claim 7 or 8.
10. An electrochemical device, characterized in that: It comprises the pole piece as claimed in claim 9.
Citation Information
Patent Citations
Artificial graphite negative electrode material with better cycle performance and preparation method thereof
CN115784221A
Secondary particle artificial graphite negative electrode material and preparation method thereof
CN115893401A